Current status and problems of second-tier banks of the Republic of Kazakhstan . - Казбеков, Б. К.; Рахимов, А. М. (Journal of Economic Research & Business Administration, 2015)
Currently, all financial reforms have already been cleaned up a lot of the legal framework engenimen state as a whole is still in need of modernization and efficiency . In order to realize the benefits of such a large amount of activity as the National Bank. If the issues are resolved in a timely manner with the increasing dominance of the banking sector in Kazakhstan believe